Identification of Bioactive Compounds of Asparagus officinalis L.: Permutation Test Allows Differentiation among “Triguero” and Hybrid Green Varieties - Cecilia Jiménez-Sánchez; Fabián Pedregosa; Isabel Borrás-Linares; Jesús Lozano-Sánchez; Antonio Segura-Carretero (Molecules, 2021)
In this study, we determined the phytochemical profile of the Spanish “triguero” asparagus landrace “verde-morado” (Asparagus officinalis L.), a wild traditional landrace, and the improved “triguero” HT-801, together with two commercial green asparagus varieties. For comparison, we used reverse-phase high-performance liquid chromatography coupled with diode array electrospray time-of-flight mass spectrometry (RP-HPLC-DAD-ESI-TOF/MS) followed by a permutation test applied using a resampling methodology valid under a relaxed set of assumptions, such as i.i.d. errors (not necessarily normal) that are exchangeable under the null hypothesis. As a result, we postulate that “triguero” varieties (the improved HT-801 followed by its parent “verde-morado”) have a significantly different phytochemical profile from that of the other two commercial hybrid green varieties. In particular, we found compounds specific to the “triguero” varieties, such as feruloylhexosylhexose isomers, or isorhamnetin-3-O-glucoside, which was found only in the “triguero” variety HT-801. Although studies relating the phytochemical content of “triguero” asparagus varieties to its health-promoting effects are required, this characteristic phytochemical profile can be used for differentiating and revalorizating these asparagus cultivars.